PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, KEPEMILIKAN MANAJERIAL, LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris Pada Perusahaan Pertambangan dan Pertanian yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Siti Iswahyuni; Enni Savitri; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to obtain empirical evidence on the influence of profitability, corporate growth, managerial ownership, leverage, liquidity, and firm size against dividend policy (Empirical Studies In Mining and Agriculture companies listed in Indonesia Stock Exchange Year 2013-2016). This research uses purposive sampling technique where this research take data of mining and agriculture company that listed in Indonesia Stock Exchange (BEI) in year 2013- 2016. The population of this research is as many as 59 companies with selected samples of the population based on the research criteria that is as many as 10 companies sampled. The analysis technique used is multiple regression analysis using SPSS for windows version 23. The result of this research indicates that managerial ownership influence to dividend policy at P <0,05 (P = 0,001), Leverage influence to dividend policy at P <0,05 (P = 0,041), and Liquidity influence to dividend policy at P <0 , 05 (P = 0.007). Meanwhile, profitability does not affect dividend policy at P> 0,05 (P = 0,297). Growth growth does not affect dividend policy at P> 0,05 (P = 0,173) and firm size does not affect dividend policy at P> 0 , 05 (P = 0.633). Adjustd R square shows the value of 0.324. This indicates that 32.4% profitability, firm growth, managerial ownership, leverage, liquidity, and firm size are influenced by the determinant variables in the model while the remaining 67.6% is explained by other variables not included in the research model.Keywords : Profitability, Corporate Growth, Managerial Ownership, Leverage, Liquidity, Company Size, Dividend Policy